2021
DOI: 10.1111/bcp.14716
|View full text |Cite
|
Sign up to set email alerts
|

Pilot drug and therapeutic committee programme in Sierra Leone: A descriptive mixed method study

Abstract: Aims Irrational medicine use is a global crisis, but incidences are proportionately higher in low‐ and middle‐income countries such as Sierra Leone. This study explores the structure, functions and challenges of drug and therapeutics committees (DTCs), an intervention towards irrational medicine use recently piloted in Sierra Leone. Methods A 2‐phase mixed‐method study design was used in this study. Firstly, a cross‐sectional survey was conducted on all pharmacists who have worked for at least 1 year in DTC‐pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…Conducting a regular meeting is one of the criteria for the functionality of DTC, in line with this our study found that the majority (82%) of the facilities conduct regular meetings which is slightly higher than a study conducted in UK (77%) 26 . However, a study conducted in Jordan stated, it was only two-thirds of DTCs (66%) met and conducted regular meetings 22 , 23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Conducting a regular meeting is one of the criteria for the functionality of DTC, in line with this our study found that the majority (82%) of the facilities conduct regular meetings which is slightly higher than a study conducted in UK (77%) 26 . However, a study conducted in Jordan stated, it was only two-thirds of DTCs (66%) met and conducted regular meetings 22 , 23 .…”
Section: Discussionsupporting
confidence: 87%
“…The study found out that some of the challenges of DTC implementation were poor commitment of individuals and/or HFs to implement DTCs according to the requirements and lack of a regulatory body to enforce DTC establishment and implementation which makes the tasks of DTC voluntary rather than mandatory which is similar with a study conducted in Sierra Leone which found out that unmotivated DTC members and lack of recognition of DTC activities within the facilities 26 . Moreover, a study conducted in Thailand found that poor performance monitoring and erratic national directives were some of the key gaps identified 27 which is similar to the findings of our study.…”
Section: Discussionsupporting
confidence: 62%
“…It has a wide range of functions, including medication selection for the local formulary, drug information provision to medical staff, drug-use policies development and auditing, and applying standard treatment guidelines. It reduces and manages medication errors (Kabba et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is a scarcity of research related to clinical pharmacy interventions or DTC activities to optimise treatment plans and save costs during COVID-19 in LMICs, especially in intensive care units (ICUs). Encouraging multidisciplinary collaboration of pharmacists within the health system by being involved in the DTC was previously encouraged (Arredondo et al, 2021 ; Cameron et al, 2022 ; Kabba et al, 2023 ). They can act proactively in light of the goals of this committee to reduce medication errors and expenditures.…”
Section: Introductionmentioning
confidence: 99%